DAMPAK KEPEMIMPINAN KEWIRAUSAHAN PADA KINERJA UKM: EFEK MEDIASI DARI FAKTOR ORGANISASI - Riski Yuliana; Henandiva Adiel; Reyza Shafira; Amalia Wilda; Sentot Imam Wahjono (PROCEEDING UMSURABAYA, 2022)
This research empirically examines the effect of entrepreneurial leadership, entrepreneurial orientation, and technological innovation capability on SMEs' performance. Interestingly, this study investigates the mediating effects of internal organizational factors such as entrepreneurial orientation, team creativity, dynamic capabilities, and competitive advantage on the relationship between entrepreneurial leadership and SMEs' performance. The consistent PLS-SEM approach was applied to analyze valid data collected from 182 small and medium IT enterprises operating at Surabaya, Indonesia. The empirical results reveal that entrepreneurial leadership via the full mediators of team creativity, dynamic capabilities, and competitive advantages can enhance the performance of IT SMEs. While entrepreneurial orientation does not influence SMEs' business performance, technological innovation capabilities can provide some benefits. Besides, entrepreneurial orientation plays no mediation role in the relationship between entrepreneurial leadership and SMEs’ performance. Finally, the results allow us to provide meaningful insights and recommendations to manage and promote better entrepreneurial inspiration.Keywords: Business performance; Entrepreneurial leadership; Entrepreneurial orientation.